Natural Resources Biometrics - Kiernan, Diane; Open Textbook Library (Open Textbook Library, 2014)
Natural Resources Biometrics begins with a review of descriptive statistics, estimation, and hypothesis testing. The following chapters cover one- and two-way analysis of variance (ANOVA), including multiple comparison methods and interaction assessment, with a strong emphasis on application and interpretation. Simple and multiple linear regressions in a natural resource setting are covered in the next chapters, focusing on correlation, model fitting, residual analysis, and confidence and prediction intervals. The final chapters cover growth and yield models, volume and biomass equations, site index curves, competition indices, importance values, and measures of species diversity, association, and community similarity.
Chapter 1: Descriptive Statistics and the Normal Distribution -- Chapter 2: Sampling Distributions and Confidence Intervals -- Chapter 3: Hypothesis Testing -- Chapter 4: Inferences about the Differences of Two Populations -- Chapter 5: One-way Analysis of Variance -- Chapter 6: Two-way Analysis of Variance -- Chapter 7: Correlation and Simple Linear Regression -- Chapter 8: Multiple Linear Regression -- Chapter 9: Modeling Growth, Yield, and Site Index -- Chapter 10: Quantitative Measures of Diversity, Site Similarity, and Habitat Suitability
In English.
Description based on print resource
Keywords: Science -- Textbooks